The Influence of Educational Background and Teaching Experience on Teachers' Self-Efficacy in Implementing Inclusive Education at Raudhatul Athfal in Semarang Regency - Isfiastuti, Nuri; Formen, Ali; Sunawan, Sunawan (Jurnal Pendidikan Islam, 2024)
Purpose – This study aims to analyze the differences in the self-efficacy of Raudhatul Athfal (RA) teachers in implementing inclusive Early Childhood Education (ECE) in Semarang Regency, considering their educational background and teaching experience. The focus of this research is to understand the extent to which these two variables influence teachers' confidence in delivering inclusive education, which is a crucial element for the success of education for children with special needs (CSN). Design/methods/approach – This study employs a quantitative approach with a causal-comparative design, where data were collected through questionnaires distributed to 115 RA teachers across 16 institutions in Semarang Regency. The instrument used was the Teacher Efficacy for Inclusive Practices (TEIP), which has been tested for validity and reliability. The data were analyzed using two-way analysis of variance (ANOVA) to evaluate the impact of educational background and teaching experience on teachers' self-efficacy. Findings – The findings indicate significant differences in teachers' self-efficacy based on educational background and teaching experience (P < 0.05). Teachers with an S1 (Bachelor's Degree) in Early Childhood Education (PAUD) have higher self-efficacy levels compared to those with a high school/vocational school (SMA/SMK) background and a general S1 (Bachelor's Degree). Moreover, more than five years of teaching experience correlates with an increase in teachers' self-efficacy in managing inclusive education. Research implications – This research contributes to the limited literature on teacher self-efficacy in the context of inclusive ECE within RA institutions under the Ministry of Religious Affairs. The study provides new insights into the factors that influence teachers' confidence in managing inclusive education, particularly in early childhood education.